Analisis karakteristik kunci yang mempengaruhi kualitas audit - Idawati, Wiwi (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2018)
The aim of this research was to get the empirical evidence about the effect of professionalism, integrity, and audit fee on quality audit. This research uses causal-comparative method with primary data that acquired from the distribution of questionairres. The research population was 255 Public Accounting Firm (KAP) in DKI Jakarta are registed at IAPI, and sample in this research was 41 Public Accounting Firm (KAP) in DKI Jakarta, with a simple random sampling technique. Researcher managed to collect 177 respondents from 41 Public Accounting Firm (KAP). Data analysis was used multiple linear regression. Based on the research, variable professionalism, integrity, and audit fee variable have simultaneously effect on quality audit.